Glaciological problems set by the control of dangerous lakes in Cordillera Blanca, Peru. III. Study of moraines and mass balances at Safuna - Lliboutry, Louis (1977)
We explain how preliminary results concerning the internal constitution of the big push moraine at Safuna were obtained in 1967. Cross-sections which were obtained later through electrical and seismic exploration and arduous borings are given. Under the lake Safuna Alta there exists a layer of dead ice which is probably a remnant from an old glacier advance and over which the active glacier slides, but this dead ice does not extend into the push moraine. Since 1950 Safuna Alta has formed, the glacier tongue has lowered by 0.8 m per year on average, and the big push moraine has moved and settled. The annual balance on the glacier tongue was measured in 1968. It increases by 3.9 m of ice per 100 m in altitude. The discharge of ice near the lake and the annual balance further up-valley allow an estimate of the mean annual balance in the accumulation zone (between 4850 and 6020 m) at 2.30 m of water per year. Until now no annual precipitation higher than 1 m/year had been measured in Cordillera Blanca, but this Cordillera includes many meso-climates. Eight successive moraines are found at Safuna. They are tentatively correlated with the eight existing between Huaraz and Laguna Llaca. Clapperton's (1972) “group 4” was not formed during the 20th, but during the 17th century. His “group 3” is not from A.D. 1750-1800, but is rather 5 000 to 7 000 years old, according to the offset of Cordillera Blanca great fault.